Audit Risk Disclosures, Targeted Inspections, and Audit Quality - Lee, Kyungha; Menon, Rahul (Contemporary Accounting Research, 2026)
ABSTRACT This article studies how the mandatory disclosure of audit risk and targeted regulatory inspections influence audit quality. We develop a model in which the auditor tests a firm's internal control over financial reporting before auditing the financial report and must issue an opinion on both. Due to higher regulatory scrutiny received by audits with weak internal control opinions, we show that targeted inspections generate countervailing effects: they reduce the auditor's internal control audit effort while increasing substantive testing effort. We show that a positive level of targeted inspections can improve audit quality when the level of random inspections is high. Furthermore, we show that targeted inspections are not always consistent with risk‐based inspections, due to the auditor's strategic response to the oversight measures. Nevertheless, such targeting can still result in higher audit quality. Our results suggest the need to exercise caution when using audit risk disclosures as a basis for enforcement.